15‐F2t‐Isoprostane Concentrations and Oxidant Status in Lactating Dairy Cattle with Acute Coliform Mastitis. (14th November 2015) - Mavangira, V.; Mangual, M.J.; Gandy, J.C.; Sordillo, L.M.
Abstract : Background: Severe mammary tissue damage during acute coliform mastitis in cattle is partially caused by oxidative stress. Although considered a gold standard biomarker in some human conditions, the utility of 15‐F2t ‐Isoprostanes (15‐F2t ‐Isop) in detecting oxidative stress in dairy cattle has not been validated. Hypothesis: Concentrations of 15‐F2t ‐Isop in plasma, urine, and milk correlate with changes in oxidant status during severe coliform mastitis in cattle. Animals: Eleven lactating Holstein‐Friesian dairy cows in their 3rd–6th lactation. Methods: A case–control study using cows with acute coliform mastitis and matched healthy controls were enrolled into this study. Measures of inflammation, oxidant status, and redox status in plasma and milk samples were quantified using commercial assays. Plasma, urine, and milk 15‐F2t ‐Isop were quantified by liquid chromatography/tandem mass spectrometry (LC‐MS/MS) and ELISA assays. Data were analyzed by Wilcoxon rank sum tests (α = 0.05). Results: Plasma 15‐F2t ‐Isop quantified by LC‐MS/MS was positively correlated with systemic oxidant status ( r = 0.83; P = .01). Urine 15‐F2t ‐Isop quantified by LC‐MS/MS did not correlate with systemic oxidant status, but was negatively correlated with redox status variables ( r = −0.83; P = .01). Milk 15‐F2t ‐Isop quantified by LC‐MS/MS was negatively correlated ( r = −0.86; P = .007) with local oxidant status. Total 15‐F2t ‐Isop in milk quantified by a commercial ELISA (cbELISA) was positively correlated with oxidant status in milk ( r = 0.98; P < .001). Conclusions and Clinical Importance: Free plasma 15‐F2t ‐Isop quantified by LC‐MS/MS and total milk 15‐F2t ‐Isop quantified by cbELISA are accurate biomarkers of systemic and mammary gland oxidant status, respectively. Establishing reference intervals for free and total 15‐F2t ‐Isops for evaluating oxidative stress in dairy cows should currently be based on the LC‐MS/MS method.